Life Cycle Cost Analysis: Beginning Stage (Part 2) - Ayob, Mohd Fairullazi (2017)
This is the 2nd part of Teaching Modules of LCC Analysis for beginners to learn the practice of Life Cycle Cost (LCC) Analysis.